PERANCANGAN UI/UX WEBSITE TANGAN BAIK MENGGUNAKAN METODE DESIGN THINKING - Ayunda, Nauralia Syifa; Waluyo, Retno; Yunita, Ika Romadoni; Riyanto, Riyanto (JURNAL REKAYASA INFORMASI, 2024)
The development of information technology today is very rapid. Information technology currently has many innovations that can make it easier to carry out a job or activity. One example of information technology innovation is applied in donations and fundraising. Tangan Baik is a website-based information system that aims to make it easier for donors to make donations and raise funds easily and quickly. User interfaces are created to make information technology easier for users to use. Good user interface design and a great user experience on a website will keep visitors on the website. Conversely, if a website has a bad interface design or user experience, users will feel uncomfortable and leave the website. In designing the UI/UX of the Tangan Baik website, creating an interface prototype design using the Figma application. The method used to design the UI/UX of the Tangan Baik website uses the Tingking Design method which has 5 phases, namely Empathize, Define, Ideate, Prototype and Testing. This research displays the results of designing the interface design of the Tangan Baik website which is in accordance with user needs, so that later the Tangan Baik website can be further developed and users can more easily understand and understand the use of this website.